Superhydrophobic membrane from double co-crystallization for high-performance separation of water-in-oil emulsion - Hou, Caiyun; Liu, Weifan; Du, Lei; Li, Yao; Zhou, Jiti; Lin, Shihong; Qiao, Sen; Zhu, Yuzhang (Journal of membrane science, 2023)
Membrane filtration has been actively explored as a promising technology for efficient water-in-oil (W/O) emulsions separation in petrochemical industries and oily wastewater treatment. However, commercial hydrophobic membranes face the challenges of low selectivity and low permeance in highly stable (surfactant-stabilized) W/O emulsions separation and suffer from membrane fouling. Here, we developed a superhydrophobic polyvinylidene fluoride (PVDF) membrane via a facile and eco-friendly solute and solvent co-crystallization (SSCC) method and successfully separated a wide range of (surfactant-stabilized) W/O emulsions. A hierarchical micron/nanostructure was constructed during the co-crystallization of microscale pristine PVDF and nanoscale defluorinated PVDF in dimethyl sulfoxide solution. With high surface roughness, low surface energy, and high porosity, the superhydrophobic membrane demonstrated excellent water droplets rejection and high oil permeance (∼70 L m−2 h−1 Pa−1), which was higher than conventional membranes during the gravity-driven separation of (surfactant-stabilized) W/O emulsions. In addition to exceptional separation performance, this membrane had high chemical stability and fouling resistance and was applicable to W/O emulsions separation under a wide range of pH and temperature conditions. [Display omitted] •The superhydrophobic membrane was fabricated by the co-crystallization process.•The membrane exhibited high permeance and fouling resistance.•The membrane exhibited outperforming separation ability of water in oil emulsion.